Conserved ecophysiology despite disparate microclimatic conditions in a gecko. Issue 4 (24th December 2021) - Schwarz, Rachel; Dror, Liat; Stark, Gavin; Gefen, Eran; Kronfeld‐Schor, Noga; Chapple, David G.; Meiri, Shai
Abstract: Microscale differences in the habitats organisms occupy can influence selection regimes and promote intraspecific variation of traits. Temperature‐dependent traits can be locally adapted to climatic conditions or be highly conserved and insensitive to directional selection under all but the most extreme regimes, and thus be similar across populations. The opposing slopes of Nahal Oren canyon in the Carmel Mountains, Israel, are strikingly different: the south‐facing slope receives intensive solar radiation, is hot and supports mostly annual vegetation, whereas the north‐facing slope is 10°C cooler, more humid, and supports Mediterranean woodland. We examined whether these differences manifest in the thermal physiology of a common gecko species Ptyodactylus guttatus in controlled laboratory conditions. We predicted that geckos from the hotter south‐facing slope would prefer higher temperatures, have faster gut passage times, lower metabolic and evaporative water loss rates, and start diel activity earlier compared with north‐facing slope conspecifics. Contrary to these predictions, there were no differences between any of the ecophysiological traits in geckos from the opposing slopes. Nevertheless, our data showed that individuals from the north‐facing slope were generally more active in earlier hours of the afternoon compared with south‐facing individuals. We suggest that P. guttatus individuals disperse between the slopes and either gene‐flow or behavioral plasticity deter local adaptation, resulting in similar physiological traits. Perhaps a stronger contrast in climatic conditions and a stronger barrier are needed to result in interpopulation divergence in temperature‐dependent traits. Abstract : Boxplots of mean preferred body temperature between the south‐facing slope (orange) and north‐facing slope (green) were measured in the field, and calculated over 1 and 20 h in the laboratory. Research Highlights: Similar ecophysiological traits of gecko populations across slopes of the same canyon, despite contrasting microclimatic conditions. Gene‐flow or behavioral plasticity mask local adaptation of ecophysiological traits to adjacent microclimates.